0794 Understanding Barriers and Communication Behaviors Impacting Referral to Sleep Surgery: Qualitative Patient Perspectives. (25th May 2022) - Ikeda, Allison; McShay, Crystina; Marsh, Robin; Saini, Shireen; Weaver, Edward
Abstract: Introduction: Shared decision-making is a process when patients, families, and clinicians work together to make optimal, personalized medical choices in the face of more than one reasonable treatment option. These interactions can influence the joint decision and may have lasting impressions for future healthcare encounters. Considering the American Academy of Sleep Medicine's recent clinical practice guideline on the referral of adults with obstructive sleep apnea (OSA) for surgical consultation, we aimed to understand patient experiences, in terms of barriers and communication behaviors in the referral process to sleep surgery consultation. Methods: We performed a qualitative study consisting of in-depth semi-structured virtual interviews with adult patients (aged ≥18 years) with OSA (apnea-hypopnea index ≥5 events per hour of sleep, scored by AASM-accredited standards) and who were recommended for sleep surgery at a tertiary Sleep Surgery Clinic. Open ended questions focused on patient experiences during healthcare encounters from diagnosis, trials with noninvasive management options and ultimate referral to sleep surgery. The interviews were audio-recorded, transcribed, and analyzed using content analysis to identify themes. Results: Ten adult patients with OSA who were evaluated in sleep surgery clinic were approached and enrolled from March through April 2021. Barriers to sleep surgery clinic included delays in OSA diagnosis due to limited OSA awareness and perceived inconvenience of sleep study, providers faulting patient for persistent sleep symptoms, patient-reported lack of urgency by providers in troubleshooting noninvasive management options, scheduling delays and waitlists, and cost. Patients were open to trialing noninvasive treatment options, though opportunities for reevaluation and shared decision-making may address unmet needs, as inadequate improvements led to frustration after multiple encounters. Patients appreciated providers who were empathetic and provided information sharing, in terms of transparent and understandable explanations. Conclusion: This study focused on experiences of patients with OSA and barriers faced to reach sleep surgery consultation. Improved communication structure to discuss unresolved concerns and remaining management options, as well as vetted resources, would set the foundation for effective shared decision-making and timely referral for sleep surgery consultation. Support (If Any): Academy of Otolaryngology Head and Neck Surgery Resident Research Centralized Otolaryngology Research Efforts (CORE). NIH T32 DC000018.